In-situ construction of Zr-based metal-organic framework core-shell heterostructure for photocatalytic degradation of organic pollutants - Abdel Aziz, Yasmeen S.; Sanad, Moustafa M. S.; Abdelhameed, Reda M.; Zaki, Ayman H. (Frontiers in Chemistry, 2023)
Photocatalysis is an eco-friendly promising approach to the degradation of textile dyes. The majority of reported studies involved remediation of dyes with an initial concentration ≤50 mg/L, which was away from the existing values in textile wastewater. Herein, a simple solvothermal route was utilized to synthesize CoFe2O4@UiO-66 core-shell heterojunction photocatalyst for the first time. The photocatalytic performance of the as-synthesized catalysts was assessed through the photodegradation of methylene blue (MB) and methyl orange (MO) dyes at an initial concentration (100 mg/L). Under simulated solar irradiation, improved photocatalytic performance was accomplished by as-obtained CoFe2O4@UiO-66 heterojunction compared to bare UiO-66 and CoFe2O4. The overall removal efficiency of dyes (100 mg/L) over CoFe2O4@UiO-66 (50 mg/L) reached >60% within 180 min. The optical and photoelectrochemical measurements showed an enhanced visible light absorption capacity as well as effective interfacial charge separation and transfer over CoFe2O4@UiO-66, emphasizing the successful construction of heterojunction. The degradation mechanism was further explored, which revealed the contribution of holes (h+), superoxide (•O2−), and hydroxyl (•OH) radicals in the degradation process, however, h+ were the predominant reactive species. This work might open up new insights for designing MOF-based core-shell heterostructured photocatalysts for the remediation of industrial organic pollutants.